Feeding Prosperity: How Youth and Women Cooperatives Revolutionised Livestock Feed in Rural Ethiopia - Rudiger, Udo; Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2024)
Feed is a critical component of livestock production systems, directly influencing the growth, health, productivity of animals and overall profitability. In Ethiopia, where mixed farming systems dominate, efficient feed processing and effective marketing strategies are essential to ensure a steady supply of high-quality feed from locally available feed resources. This not only boosts livestock productivity but also contributes to the overall sustainability and profitability of mixed farming system.